Baby Paradise Enterprise - Anuar, Nur Syahmina; Rosli, Nur Shahanim; Mohd Ruslan, Nur Nabilah; Ahmad Tarmidi, Siti Najihah; Mahmud, Muhammad Syazni; Hakim Bin Isa, Muhammad Luqman (2016)
This abstract introduces entrepreneurship as a process of innovation and new venture creation across four dimensions: individual, organization, environment, and institution. It defines entrepreneurs as individuals who actively form, lead, and nurture their businesses for growth. Baby Paradise Enterprise is a business developed to provide baby spa services for infants aged five months up to four years old. The company is structured as a partnership involving six partners, each contributing an equal capital of RM 20,000. Each partner holds a distinct managerial position and responsibility. Baby Paradise Enterprise focuses on offering various baby spa services and packages. Recognizing the increasing demand for baby spa services and the low number of existing providers in Malaysia, the partners chose to establish the business in Shah Alam to meet this market need. The long-term goal is to expand Malaysia's baby spa industry through this venture, with the ambition of becoming one of the nation's leading entrepreneurs in the service industry by ultimately breaking into the international market.